Functional and sensory properties of olives fortified spreadable cheese - Maja Repajić; Anamarija Grudenić; Branka Levaj (Mljekarstvo)
The aim of this work was to investigate the influence of olive type (green and black) and content on quality and sensory properties of spreadable cheese with olives. Total solids, pH value, colour (colourimetric), total phenols by Folin-Ciocalteau method and antioxidant capacity (FRAP) of the raw materials as well as of the prepared samples were examined. Furthermore, samples of spreadable cheese with olives were sensory evaluated using the Quantitative Descriptive Analysis (QDA). ANOVA showed that the applied sources of variation significantly affected the majority of investigated parameters. Samples with black olives had slightly higher dry matter content and pH value, and were characterized by darker and dull colour. The determined total phenols contents and antioxidant capacity showed a good potential of spreadable cheese with olives as a functional food, whereby green olives samples had higher total phenols content as well as antioxidant capacity. Generally, sensory properties of all samples were very well scored, indicating their good acceptability by consumers. Samples with black olives accomplished higher scores for flavour harmony and overall acceptability, where spreadable cheese with the highest olive content emphasized with the highest scores for these properties.